Mechanical performances of mortar prisms and concrete slabs incorporating rubber aggregates. (September 2018) - Fantilli, Alessandro P.; Chiaia, Bernardino
Highlights: Rubber particles are used herein to substitute the aggregates of concrete and mortars. Three point bending tests are performed on mortar prisms and concrete slabs. The results of the tests depend on the structural scale and particle size. Fracture toughness always increases in presence of rubber. For large particle size, the increment of ductility can increase the flexural strength. Abstract: To reduce the environmental impact of cement-based composites used by the construction industry, stone aggregates can be substituted by unconventional aggregates, such as the rubber from end-of-life tyres. This substitution strategy can be applied to both mortars and structural concretes. Nevertheless, each application requires a specific particle size distribution, to the point that the maximum aggregate size of concrete can be 10 times larger than that of mortar. Consequently, the mechanical response under bending actions, ruled by the fracture energy, can drastically change with the structural dimension. This size-effect is particularly evident in the experimental analyses performed herein, which include three point bending tests on mortar prisms and concrete slabs. As a result, the fracture toughness always increases in presence of rubber, and in the case of large particle size the increment of ductility can lead to the increment of the flexural strength. Graphical abstract: Image, graphical abstract